Pemberdayaan Masyarakat Melalui Surveilans Epidemiologi Partisipatif Dalam Pencegahan Wabah - Sahabuddin, Sahabuddin; Idris, Idris; Nursinah, Nursinah (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Infectious disease outbreaks remain a public health threat that can have widespread impacts if not addressed quickly and appropriately. One effective approach to prevention is participatory epidemiological surveillance (SEP), which involves active community involvement in the detection, reporting, and prevention of infectious diseases. This community service activity aims to increase community capacity to recognize infectious disease symptoms, report suspicious health events, and implement community-based preventive measures. The methods used include outreach, health cadre training, case reporting simulations, and evaluation of community understanding. The results of the activity show a significant increase in community knowledge and skills related to early detection and participation in outbreak prevention. It is hoped that this activity will strengthen community-based health systems and increase community resilience to the threat of infectious diseases.